2017
DOI: 10.1590/0100-3984.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric study of the knee in patients with osteoarthritis: intraoperative measurement versus magnetic resonance imaging

Abstract: Objective:To compare intraoperative measurements of the knee with those obtained by magnetic resonance imaging, in order to validate the latter method for use in anthropometric studies.Materials and Methods:We studied 20 knees in 20 patients with osteoarthritis, all of whom underwent total arthroplasty between August and December of 2013. We took six measurements in the distal femur and two in the proximal tibia. Using the information system of the institution, we made the measurements on magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Most authors have only looked at the AP and ML dimensions for the distal femur and proximal tibia [ 5 , 6 , 12 , 24 ]. The ROC of the femoral condyles and proximal tibia are not uniform and are integral in dictating normal knee motion as the curvature of the condyles is one of the main factors affecting knee kinematics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors have only looked at the AP and ML dimensions for the distal femur and proximal tibia [ 5 , 6 , 12 , 24 ]. The ROC of the femoral condyles and proximal tibia are not uniform and are integral in dictating normal knee motion as the curvature of the condyles is one of the main factors affecting knee kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have used specimen resected during surgery for anthropometric measurements [ 18 , 24 ]. The specimens obtained during knee arthroplasty surgery are obviously arthritic and may not be suitable for basing implant design.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have found that osteoarthritis patients have immune abnormalities, and abnormal secretions of cytokines might damage cartilage function and metabolism[14,15]. In addition, aggravated gradual decomposition of cartilage matrix can bring irreversible injury to the joint structure of patients, which is manifested as the corresponding clinical symptoms, thus accelerating the progress of articular cartilage injury[16,17]. IL-1β, IL-6 and TNF-α are secreted from macrophages and immune cells, which mainly come from the lining cells of the synovial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the excellent tissue contrast provided by MRI, it can reveal musculoskeletal changes that are not visible on X-rays, as well as allowing the identification of the lesions that are most suitable for biopsy ( 1 , 8 - 11 ) . On MRI, nodular sarcoidosis has a characteristic appearance that can facilitate its accurate diagnosis-it typically consists of central areas of fibrosis that show low signal intensity in all sequences, together with peripheral areas of granulomas that show high signal intensity in T2weighted sequences and contrast enhancement ( 1 , 6 ) -findings collectively known as a "black star".…”
mentioning
confidence: 99%